PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) UNTUK MENINGKATKAN KEMAMPUAN MENYELESAIKAN SOAL CERITA DAN SIKAP SISWA - Zikra Hayati (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2012)
This research was conducted on 60 pupils at fourth level in an Elementary School in Banda Aceh (MIN 1 Banda Aceh). Comparing to other schools in Aceh, the school has a good quality, in this case middle ability of the grade students, than others. The experimental design both qualitative and quantitative approaches, in order to investigate students’ abilities to solve word problems. There are two groups, namely, experimental group which using realistic mathematics education (RME) approach in instruction , and another group without using RME in instruction. in the case using instrument, both groups used the same instrument in this research. Moreover, eksperimental case research Pre-test Post-test Control Group Design was used, in order to investigate differences between student who has ability to solve word problem by using RME approach and student who get instructions without RME approach and so to know interaction between students ability to solve word problem by mathematics realistic. The investigation based on the level ability mathematics students (high level, medium level and low level), and to see students’ attitude toward mathematics realistic. Based on data analysis, it is found that a differences of students abilities between experimental group and control group. The differences of the abilities shown by statistics test by anova test (by using α = 0,05). It means that there are differences of students’ abilities to solve word problems using RME and students’ ability to word word problems using conventional learning as learning instructions.therefore, there is no interaction between students’ abilities in order to solve word problems in RME based on students’ abilities (high level, medium level and low level) and students’ attitude toward RME approach.